AUTHOR MARKS IN EXTREMIST TEXT (The Role of Exact Sciences in the Era of Modern Development, 2024)
This study investigates the linguistic and rhetorical markers in extremist texts, focusing on the strategies employed by authors to radicalize and mobilize their audience. Utilizing a mixed-methods approach, we analyzed a diverse corpus of 100 extremist texts through qualitative content analysis and quantitative linguistic techniques. The findings reveal distinct patterns, including the use of polarizing language, victimhood narratives, glorification of violence, and appeals to identity. These patterns were quantified using natural language processing (NLP) tools, which confirmed the high frequency of polarizing terms and negative sentiment towards out-groups. The study highlights the critical role of language in the spread of extremist ideologies and provides valuable insights for the development of targeted counter-narratives and early intervention strategies.